2022
DOI: 10.1111/aej.12734
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of different Nickel–Titanium rotary and reciprocating root canal preparation systems on the amount of apically extruded debris

Abstract: This study aimed to evaluate the amount of apically extruded debris caused by different NiTi files. One hundred mandibular premolars were included in this study. The specimens were divided into five groups (n = 20): (i) TruNatomy, (ii) WaveOne Gold, (iii) 2Shape, (iv) ProTaper Next and (v) Reciproc Blue. The extruded debris was collected into preweighed Eppendorf tubes. These tubes were weighed again, and the net weight of debris was calculated. Data were statistically analysed, and the significance level was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Apical extrusion of debris is an inherent side effect during the process of root canal preparation. All the instrumentation techniques were found to be associated with apical debris extrusion in this study, which aligns with previous investigations [ 20 22 ]. The quantity of extruded debris is subject to variation depending on the design and kinematics of the instrument [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…Apical extrusion of debris is an inherent side effect during the process of root canal preparation. All the instrumentation techniques were found to be associated with apical debris extrusion in this study, which aligns with previous investigations [ 20 22 ]. The quantity of extruded debris is subject to variation depending on the design and kinematics of the instrument [ 5 , 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…However, upon examining the literature, no study was found that compared the rotary file systems (TRN, PTUltimate, and VDW.R) used in this study together. In addition, studies involving root canal preparation with rotary files have reported that apical extrusion of debris cannot be prevented (16,18,23). The occurrence of debris extrusion in all samples of the three file systems tested in our study is in line with other studies.…”
Section: Discussionsupporting
confidence: 91%
“…The amount of debris extruded apically is influenced by many factors, such as the size, taper, design, crosssectional shape, and kinematics of the instrument used in chemomechanical preparation (23). Numerous studies exist regarding the apical extrusion of debris by rotary files used in chemomechanical preparation (16,18,23). However, upon examining the literature, no study was found that compared the rotary file systems (TRN, PTUltimate, and VDW.R) used in this study together.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…All instrumentation techniques result in debris extrusion (24,25), possibly one of the main causes of postoperative pain (26). TN has been reported to produce relatively small amounts of apically extruded debris (25,27), and recent systematic reviews showed that both UI and CH reduced postoperative pain (6, 7). However, the results of this study suggested that the intensity of post-instrumentation pain in the MP group did not differ from those of the CP group at any assessed time points.…”
Section: Discussionmentioning
confidence: 99%